2011
DOI: 10.4103/0970-1591.85454
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic neurofibroma arising from prostate in a case of neurofibromatosis-1

Abstract: Pelvic neurofibroma is a rare condition and can be associated with neurofibromatosis-1 (NF-1). The diagnosis is primarily based on histopathology, though certain characteristic imaging features like the ‘target sign’ on T2W MRI are highly suggestive of the diagnosis. We describe a case of pelvic plexiform neurofibroma in a case of NF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Pelvic PNF is a rare entity, and around 60 cases have been reported so far in the published literature. 2 It usually involves the nerve plexuses near the urinary bladder followed by involvement of the prostate, seminal vesicle and urethra in males and vagina or urethra in females. 5 The majority of these lesions are asymptomatic, and symptoms, if present, are due to the mass effect on adjacent structures or malignant infiltration, which is seen in up to 30% cases of pelvic PNFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic PNF is a rare entity, and around 60 cases have been reported so far in the published literature. 2 It usually involves the nerve plexuses near the urinary bladder followed by involvement of the prostate, seminal vesicle and urethra in males and vagina or urethra in females. 5 The majority of these lesions are asymptomatic, and symptoms, if present, are due to the mass effect on adjacent structures or malignant infiltration, which is seen in up to 30% cases of pelvic PNFs.…”
Section: Discussionmentioning
confidence: 99%
“…PNF has a preponderance for the craniomaxillofacial region, 1 but involvement of the genitourinary tract is rare. 2 The presenting symptoms of PNF mainly depend on the location of the lesion. The pelvic neurofibroma usually presents with lower urinary tract symptoms and bowel dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Here it shows a presentation with neural pain. Manish et al 1 presented a case of a 12 year old male child with urinary obstruction found to have a prostatic neurofibroma. Nadkarni et al 4 presented case of a 4-year old boy with low-back pain that radiated bilaterally into the L-4 and L-5 dermatomes; intraoperatively, a solid mass, which engulfed the entire cauda equina, could not be dissected from the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Only 60 cases of pelvic neurofibroma have been reported till date. 1 , 2 We report this case of a pelvic neurofibroma in a 58-year old male, which mimicked a soft tissue tumor on presentation.…”
Section: Introductionmentioning
confidence: 92%
“…34,35 Other lesions A variety of other mesenchymal and spindle cell lesions have been reported to occur very rarely in the prostate. These include: angiosarcoma, 56 hemangioma, 57,58 hemangioendothelioma, 59 pleomorphic undifferentiated sarcoma, 60,61 synovial sarcoma, 62 malignant peripheral nerve sheath tumor, 63,64 neurofibroma, 65 and granular cell tumor. 66…”
Section: Mixed Epithelial-stromal Tumor Of Seminal Vesiclementioning
confidence: 99%